Production and Characterization of Bilayer Tissue Scaffolds Prepared with Different Alginate-Salts and Fibroin - ÇELİK, Özge; MOHAMED, Salma A. Taher; EMİN, Nuray (Gazi University, 2022)
The presented study aimed to design and characterize bilayer Alginate/Fibroin scaffolds to provide faster and higher quality treatment of skin tissue losses with tissue engineering approach. In this context, it was tried to form the dermis and epidermis layers with alginate salts (sodium and calcium) and fibroin with a biomimetic approach, and it was aimed to determine the most suitable alginate salt-fibroin composite scaffold by trying different production methods. The optimum design was determined by macroscopic measurement and dimensional analysis of the scaffolds produced by four different methods and their chemical structures were controlled with FTIR. Among the produced scaffolds, calcium alginate/fibroin (CaAlg/Fb) scaffolds were determined to have the most suitable morphological and chemical structure. With further characterization, the pore distribution and size were examined by SEM analysis and it was determined that surface pore diameters vary from 30 µm to 300 µm which are suitable for cell settlement. The thermal stability of the structure was determined by thermal gravimetry, and the degradation rate was calculated from the thermograms. According to the TG analysis, decomposition of the CaAlg/Fb scaffolds occurs much faster with temperature than homo-biopolymeric (CaAlg and Fb) structures. As a result, it was found that bilayer CaAlg/Fb scaffolds were capable of forming full-thickness dermal and/or also osteochondral wound dressings both morphologically and structurally. It is recommended to perform the tissue forming ability of this scaffold structure by performing advanced biological analyzes.
Keywords: Silk Fibroin; Alginate; Tissue Scaffold; Biomimetic Patch; Lyophilization